Cost-benefit analysis of ballast water treatment for three major port clusters in China: evaluation of different scenario strategies - Nie, Anwei; Wan, Zheng; Shi, ZhuangFei; Wang, Zhaojun (Frontiers in Marine Science, 2023)
The expansion of maritime trade has led to the introduction of invasive species into aquatic ecosystems through ballast water discharge. China, being a major player in global trade and manufacturing, has experienced negative impacts on its coastal ecosystems and marine biodiversity. This study examines the cost-benefit trade-offs of ballast water management policies for major port clusters in China and other global ports. This paper evaluates compliance costs for individual vessels and fleets under different policy scenarios and ballast water treatment system (BWTS) installation strategies. Results suggest that the onboard BWTS installation strategy is currently more costeffective under the default IMO policy. However, if global discharge requirements become stricter or the capital and operating costs of BWTS increase significantly, installing BWTS based on port location may be more advantageous due to potential economies of scale. Ships with high ballast water discharge volumes, such as bulk carriers, may be better suited to handle potential policy transitions in the future. As China transitions to stricter regulations, the annual increase in compliance costs varies from 456 million (optimistic estimate) to 1.205 billion (pessimistic estimate). The study suggests that policymakers should take a comprehensive approach to ballast water management policies, considering the cost-benefit trade-offs between compliance costs and environmental risks. The paper also highlights the importance of evaluating the impact of potential factors such as improvements in BWTS technology, fuel consumption, emissions, and maintenance costs.